Some anthropometric measurements and their relationship to certain physical characteristics among handball players: A survey study of clubs in the capital city of Sana'a, Republic of Yemen - yahia hocine alhandi, faiz; hocine nacer al sofi, bakil (sports creativity, 2025)
This research aims to identify the relationship between certain anthropometric measurements and physical characteristics among handball players. The research sample consisted of (11) players representing the handball teams of the Capital Governorate, namely (11 May Club, Al-Wahda Club, and Al-Istibyan Club).